Older People Care Chain as Part of the Integrated Care: A Qualitative Study - Terhi Lemetti; Päivi Voutilainen; Minna Stolt; Sini Eloranta; Riitta Suhonen (UBIQUITY PRESS LTD, 2022)
Introduction: Health care systems for older people are becoming more complex and care for older people, in the transition between hospital and primary healthcare requires more systematic collaboration between nurses. This study describes nurses' perceptions of their collaboration when working between hospital and primary healthcare within the older people care chain.Theory and methods: Using a qualitative approach, informed by grounded theory, six focus groups were conducted with a purposive sample of registered nurses (n = 28) from hospitals (n = 14) and primary -healthcare (n = 14) during 2013. The data were analyzed using dimensional analysis.Findings: Four dimensions of collaboration were identified: 1) Context and Situation, 2) Conditions, 3) Processes and Interactions and 4) The Consequences of nurse-to-nurse collaboration within the older people care chain. These four dimensions were then conceptualized into a model of nurse-to-nurse collaboration.Discussion and conclusion: Improved collaboration is useful for the safe, timely and controlled transfer of older people between hospital and primary healthcare organizations and also in healthcare education. The findings in this study of nurse-to-nurse collaboration provides direction and opportunities to improve collaboration and subsequently, the continuity and integration in older people care in the transition between organizations.